PENGARUH KEPEMIMPINAN DAN DISIPLIN TERHADAP KINERJA PERSONEL PRAJURIT TNI-AD DI KODIM 1419 ENREKANG - Triska ramadani; Muliyadi Hamid; Nurmadhani Fitri Suyuti (MANOR: JURNAL MANAJEMEN DAN ORGANISASI REVIEW, 2023)
ABSTRACT The Influence of Leadership and Discipline on the Performance of TNI-AD Soldier Personnel at Kodim 1419 Enrekang Triska Ramadani Muliyadi Hamid Nurmadhani Fitri Suyuti This study aims to measure the influence of leadership on the performance of TNI-AD soldier personnel at the 1419 Enrekang District Military Command which is mediated by discipline. The collection of quantitative research data was carried out using the solvin formula sample technique on 148 populations and the results of the returned and valid questionnaire were 106 people as a sample. Data processing uses the validity and reliability test methods using the SPSS program, the testing technique that is often used by researchers to test validity is to use the Bivariate Pearson correlation (personal moment product) and to use the questionnaire reliability test method. In this study, the split half item method was divided into two groups, namely groups of odd items and groups of even items. Then each group's score for each item is added up to produce a total score. If the correlation is 0.7, it is said that the item provides a sufficient level of reliability, conversely, if the correlation value is below 0.7, it is said that the item is less reliable. The results of this study concluded that leadership and discipline affect performance. The researchers prove this with a value (f count) of 19.078 > 3.08 with f table with a significance value of 0.000 <0.05 meaning that leadership and discipline simultaneously influence performance. Keywords: Leadership, Discipline, and Performance